Alternative Framings, Countervailing Visions: Locating the "P" in Professional Identity Formation. (February 2016) - Hafferty, Frederic W.; Michalec, Barret; Martimianakis, Maria Athina (Tina); Tilburt, Jon C.
Abstract : Professional identity formation in medical education is referenced increasingly as an object for educational reform. The authors introduce core concepts from two largely untapped literatures on identity and formation, contrasting framings on occupational preparation from within the organizational socialization literature with issues of socialization and professional acculturation from a military sciences perspective. The organizational sciences literature emphasizes socializing a workforce to "fit in, " raising questions about how organization values might clash with core professional values concerning patient primary and social justice. The military literature, in turn, advances the notions of professional identity as a collective property, and that a particular social other (the public) must participate in shaping the group's identity as a profession . The authors extrapolate from these reviews that the training of physicians-as-professionals, and thus issues of socialization and identity formation, require intentionality and specificity around these contrasting issues. In turn, they argue that medical educators must attend to socializing trainees to a professional group identity while at the same time producing health care professionals who retain the capacity to resist the bureaucratic application of standardized solutions to contemporary problems. Educators must thus strive to identify the skills, knowledge, and attitudes necessary that will allow physicians-qua-professionals to function as a quasi-subversive work force and to disrupt the very system that helped to shape their identity, so that they may fulfill their mission to their patients.